A space vector-based current controller for doubly fed induction generators - Mohseni, M.; Islam, Syed (2009)
This paper presents the implementation of a space vector-based hysteresis current controller for the DFIG-based wind generator. The stator voltage-oriented reference frame is adopted for the DFIG modelling and control since the performance of the stator flux-oriented reference frame, as the most commonly used reference frame, is highly dependent on the accurate detection of the flux vector position. A vector-based hysteresis current controller with 3-level hysteresis comparators is utilized to regulate the current in the rotor side inverter (RSI). In contrast to ramp comparison current controller with PI regulators, the proposed current controller exhibits excellent transient performance using a simple control structure. This very fast tracking behaviour justifies the modelling of the RSI as a controlled current source, which significantly simplifies the DFIG modelling and control. The steady-state performance of the hysteresis current controller, on the other hand, is considerably improved by reducing the RSI switching frequency and minimizing oscillations in the RSI output current. Simulation studies are carried out for a 1.5-MW DFIG system to validate the proposed modeling and control method. ©2009 IEEE.